2011
DOI: 10.1021/ac2001725
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Thermal, and Electric Field Induced Unfolding of Single Protein Molecules Studied Using Nanopores

Abstract: Single-molecule experimental techniques have recently shown to be of significant interest for use in numerous applications in both the research laboratory and industrial settings. Although many single-molecule techniques exist, the nanopore platform is perhaps one of the more popular techniques due to its ability to act as a molecular sensor of biological macromolecules. For example, nanopores offer a unique, new method for probing various properties of proteins and can contribute to elucidating key biophysica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
132
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(144 citation statements)
references
References 40 publications
9
132
3
Order By: Relevance
“…It is puzzling why the native state BSA in a nanopore produced such a broad peak in ΔI b , implying a broad distribution of the excluded volume Λ and translocation configurations. Broad range of ΔI b distributions were also observed by previous reports studying BSA and other protein translocation in solid-state nanopores [9, 1619, 21, 2527], suggesting some protein molecules going through solid-state nanopores with multiple conformations, some could be partially denatured.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…It is puzzling why the native state BSA in a nanopore produced such a broad peak in ΔI b , implying a broad distribution of the excluded volume Λ and translocation configurations. Broad range of ΔI b distributions were also observed by previous reports studying BSA and other protein translocation in solid-state nanopores [9, 1619, 21, 2527], suggesting some protein molecules going through solid-state nanopores with multiple conformations, some could be partially denatured.…”
Section: Discussionsupporting
confidence: 76%
“…However, this estimation has ignored complicated issues such as the space inside a folded protein, hydration layer and territory bound water and ions on protein surface, the real excluded volume of a protein molecule in a nanopore is expected to be larger. For example, here we calculate Λ fold =87.0 nm 3 for a folded BSA, this is smaller than the value reported by Freedman et al [25] calculated by formula Λ=(4/3)πa 2 b =117 nm 3 using the dimensions shown in Fig. 1d, and it is also smaller than experimentally measured value166±29 nm 3 .…”
Section: Principles Of Measuring Protein Unfolding By a Solid-statcontrasting
confidence: 79%
See 1 more Smart Citation
“…In the past decade, synthetic nanopores have been widely used for single molecule detection [2,[15][16][17] [17], and e-field can influence interactions between the protein and pore which can trigger protein denaturation inside a nanopore [33]. Thus, a comprehensive understanding of the conformational changes is important because of the nature of detection using ionic current measurement.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that intense electric fields can profoundly affect the physical properties and reactivity of dissolved molecules and, based on experimental results, they have been proven to play an essential role in proteins behavior, including folding, molecular recognition, and catalytic functions [14,15]. Recently, MD technique has been suggested as the best approach for shedding light on the different hypotheses on the interaction between electromagnetic fields and biological targets [16,17], for which a complete theoretical investigation is still lacking.In particular fully atomistic simulations have proven to be a valuable methodology: to study the effect of microwaves on enzymes in solution [18,19], to investigate the action of pulsed electric fields on biochemical reactions in confined environments with outcomes confirmed by the experimental data [20] and to provide insight in the dynamic behavior of small peptides dispersed in water solutions, under the influences of external electric fields such as those exerted by biomedical sensors and/or field-effect transistors [21].…”
Section: Introductionmentioning
confidence: 99%